INSTIs for the management of HIV-associated TB (INSIGHT study): a phase 2b study to evaluate the efficacy, safety and pharmacokinetics of a combination of bictegravir, emtricitabine and tenofovir alafenamide fumarate for the treatment of HIV-1 infection in patients with drug-susceptible tuberculosis on a rifampicin-based treatment regimen: a phase 2b open-label randomised controlled trial. Issue 11 (10th November 2022) - Naidoo, Anushka; Dooley, Kelly E; Naidoo, Kogieleum; Padayatchi, Nesri; Yende-Zuma, Nonhlanhla; Perumal, Rubeshan; Dorse, Gillian; Boodhram, Resha; Osuala, Emmanuella Chinonso
Abstract : Introduction: Cotreatment of HIV and tuberculosis (TB) reduces morbidity and mortality in coinfected patients. Availability of antiretroviral treatment (ART) drug options, including within drug classes, is important, particularly in high HIV/TB burden low and middle-income countries. Methods and analysis: This is a phase 2b, open-label, non-comparative randomised controlled trial to assess the antiretroviral activity of a fixed-drug, single tablet, combination of bictegravir (BIC) 50 mg/emtricitabine (FTC) 200 mg/tenofovir alafenamide (TAF) 25 mg (Biktarvy). The primary objective is to determine the efficacy, safety and pharmacokinetics of two times per day, coformulated BIC 50 mg/FTC 200 mg/TAF 25 mg in HIV-positive ART-naïve patients with TB who are receiving a rifampicin-based treatment regimen and to characterise viral suppression rates at week 24 through to week 48 in the BIC/FTC/TAF arm. We will enrol 120 patients randomised in a 2:1 ratio to the intervention or control arm of the study. A non-comparative contemporaneous control arm in which participants receive a dolutegravir-based regimen (standard of care) will also be enrolled. Ethics and dissemination: The University of KwaZulu-Natal Biomedical Research Ethics Committee (BREC) and the South African Health Products Regulatory Authority (SAHPRA) have granted regulatory approval (trial reference numbers: BREC/00001300/2020 and SAHPRA 20200810). Trial results will be disseminated through conference presentations, peer-reviewed publications and the clinical trial registry. Trial registration number: Clinicaltrials.gov; Trial registration number: NCT04734652 ; South African National Clinical Trials Register (SANCTR DOH-27-012021-6789)